Delayed social imprints of good health in the social and university environment - Requeiro, Reinaldo (2019)
Introduction: The concept of delayed social imprints of good health, refers to behaviors established in people and decision makers, which tend to delay the upcoming of beneficial practices, both for interpersonal coexistence and the surrounding environment. Objective: To talk about the social elements that delay good health, in the social and university environment. Methods: A bibliographic review was made based on the analysis of 28 documentary sources, selected as determinants in the course of the theoretical construction of the definition in question. The documents were, in most cases, articles of scientific journals published in the last five years, and accessible through Pubmed, Scielo and ScienceDirect. Conclusions: The delayed imprints of good health in the social sphere and the university, constitute social ideologies that allow changes of behaviors oriented to the good adaptation and the self-care, in front of the proposals in charge of international organisms regarding to the promotion of the health.